School in Italy: a safe place for children and adolescents - Alberto Villani; Luana Coltella; Stefania Ranno; Federico Bianchi di Castelbianco; Paola Maria Murru; Rossella Sonnino; Teresa Mazzone; Livia Piccioni; Giulia Linardos; Stefano Chiavelli; Fabrizio Pontarelli; Giovanni Corsello; et al. (BMC, 2021)
Abstract Background During the first SARS-CoV-2 pandemic phase, the sudden closure of schools was one of the main measures to minimize the spread of the virus. In the second phase, several safety procedures were implemented to avoid school closure. To evaluate if the school is a safe place, students and staff of two school complexes of Rome were monitored to evaluate the efficacy of prevention measures inside the school buildings. Methods Oral secretions specimens were collected from 1262 subjects for a total of 3431 samples, collected over a 3 months period. Detection of Coronavirus SARS-CoV-2 was performed by real-time PCR. Target genes were represented by E gene, RdRP/S gene and N gene. Results Among the 3431 samples analyzed, just 16 sample resulted as positive or low positive: 1 sample in the first month, 12 samples in the second month and 3 in the third month. In each period of evaluation, all positive children attended different classes. Conclusions Even if the school has the potential for spreading viruses, our preliminary results show the efficacy of the implementations undertaken in this setting to minimize virus diffusion. Our evidence suggests that school does not act as an amplifier for transmission of SARS-CoV-2 and can be really considered a safe place for students.